Statistical Methods in Intensive Care Online Monitoring - Bauer, Marcus; Fried, Roland; Gather, Ursula; Imhoff, Michael (Universitätsbibliothek Dortmund, 2000)
Intelligent alarm systems are needed for adequate bedside decision support in critical care. Clinical information systems acquire physiological variables online in short time intervals. To identify complications as well as therapeutic effects procedures for rapid classiffication of the current state of the patient have to be developed. Detection of characteristic patterns in the data can be accomplished by statistical time series analysis. In view of the high dimension of the data statistical methods for dimension reduction should be used in advance. We discuss the potential of statistical techniques for online monitoring.
Keywords: 310